Discourse on measurement - Arthur Paul Pedersen; David Kellen; Conor Mayo-Wilson; Clintin P. Davis-Stober; John C. Dunn; M. Ali Khan; Maxwell B. Stinchcombe; Michael L. Kalish; Katya Tentori; Julia Haaf (Proceedings of the National Academy of Sciences, 2025)
Measurement literacy is required for strong scientific reasoning, effective experimental design, conceptual and empirical validation of measurement quantities, and the intelligible interpretation of error in theory construction. This discourse examines how issues in measurement are posed and resolved and addresses potential misunderstandings. Examples drawn from across the sciences are used to show that measurement literacy promotes the goals of scientific discourse and provides the necessary foundation for carving out perspectives and carrying out interventions in science.